Exploring Blended Learning Designs for Community College Courses Using Community of Inquiry Framework - Chudaeva, Elena; Blodgett, Cynthia; Loth, Guilherme; Somaskantha, Thuvaragah (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
The goal of this single-phase and convergent mixed methods study was to compare the differences in the effectiveness of the Community of Inquiry (CoI) presences of a community college blended block instructional model with the in-person counterpart. Data were gathered from the Community of Inquiry Survey, Blackboard LMS reports, and course evaluation surveys. The results indicate that students had a better overall experience with the blended course. The blended block model provided flexibility while achieving course goals. Further, findings reveal differences in all three CoI presences between the two course formats with more student awareness of the presences in the in-person course.